أثر محمد الأخضرالسائحي في صناعة المشهد الثقافي في الجنوب الشرقي قبل الاستقلال - بله باسي, بسمة; قيطون, قويدر (University of Eloued جامعة الوادي, 2022)
يعتبر محمد الأخضر السائحي (السائحي الكبير) أحد أهم أعلام الجنوب الشرقي الجزائري، الذين كان لهم دور فاعل في الساحة الثقافية والأدبية أثناء فترة الاحتلال الفرنسي، مما جعله على رأس قادة المقاومة الثقافية في الجزائر عامة وفي الجنوب الشرقي خاصة؛ سواء ما تمثل في نشاطه الثقافي في تونس وخدمته للطلاب الجزائريين هناك، أو بدوره في إنشاء التعليم في منطقة تماسين وتقرت، أو بعمله في الإعلام بعد أن انتقل إلى العاصمة، أضف إلى ذلك منجزاته المتنوعة شعرا ونثرا ذات الفاعلية في هذا الحقل، وعليه تسعى هذه المداخلة إلى النظر إلى هذا العَلم المتميز من زاوية إسهامه في المقاومة الثقافية أثناء فترة الاحتلال حتى وإن كان جهده قد امتد وبشكل مهم إلى ما بعد الاستقلال، وذلك بتناول ما يأتي: - السائحي الكبير مولدا ونشأة؛ - النشاط العلمي والثقافي في تونس؛ - أثر السائحي في المشهد العلمي والثقافي في الجنوب الشرقي؛ - النشاط الثقافي المقاوم بعد الانتقال إلى العاصمة. Abstract : Mohamed al-Akhdar al-Sayihi (the great tourist) is considered one of the most important figures in the southeast of Algeria. He had an active role in the cultural and literary arena during the period of the French revolution that made him a leader of the cultural resistance in Algeria in general and in the southeast in particular. his cultural activity were in Tunisia and in Algerian serving students there, and establishing education in the region of Tamasin and Touggort. He also worked in the media after he moved to the capital Algiers. Add to this his various achievements in poetry and prose that are effective in this field. Accordingly, this intervention seeks to look at this distinguished science from the point of view of its contribution to the cultural resistance during the period of French revution, even if its efforts extended in a way that important until after independence, by addressing the following topics: - The great tourist, born and raised. - Scientific and cultural activity in Tunisia. – - The impact of the tourist on the scientific and cultural scene in the southeast. - Resistance cultural activity after moving to the capital
Mohamed al-Akhdar al-Sayihi 's impact on the cultural scene industry in the southeast before independence
مداخلة
Keywords: محمد الأخضر السائحي؛ المشهد الثقافي؛ الجنوب الشرقي؛ قبل الاستقلال; Mohammed Al-Akhdar Al- Sayihi; cultural landscape; southeast; before independence words at most - Separated by semicolons..